The Design, Synthesis, and Evaluation of Diaminopimelic Acid Derivatives as Potential dapF Inhibitors Preventing Lysine Biosynthesis for Antibacterial Activity - Mohd Sayeed Shaikh; Mayura A. Kale; V. Muralidharan; T. Venkatachalam; Syed Sarfaraz Ali; Fahadul Islam; Sharuk L. Khan; Falak A. Siddiqui; Humaira Urmee; Ganesh G. Tapadiya; Sachin A. Dhawale; Long Chiau Ming; et al. (MDPI AG, 2022)
We created thiazole and oxazole analogues of diaminopimelic acid (DAP) by replacing its carboxyl groups and substituting sulphur for the central carbon atom. Toxicity, ADME, molecular docking, and in vitro antimicrobial studies of the synthesized compounds were carried out. These compounds displayed significant antibacterial efficacy, with MICs of 70-80 µg/mL against all tested bacteria. Comparative values of the MIC, MBC, and ZOI of the synthesized compound were noticed when compared with ciprofloxacin. At 200 µg/mL, thio-DAP (1) had a ZOI of 22.67 ± 0.58, while ciprofloxacin had a ZOI of 23.67 ± 0.58. To synthesize thio-DAP (1) and oxa-DAP (2), l-cysteine was used as a precursor for the L-stereocenter (l-cysteine), which is recognized by the dapF enzyme's active site and selectively binds to the ligand's L-stereocenter. Docking studies of these compounds were carried out using the programme version 11.5 Schrodinger to reveal the hydrophobic and hydrophilic properties of these complexes. The docking scores of compounds one and two were −9.823 and −10.098 kcal/mol, respectively, as compared with LL-DAP (−9.426 kcal/mol.). This suggests that compounds one and two interact more precisely with dapF than LL-DAP. Chemicals one and two were synthesized via the SBDD (structure-based drug design) approach and these act as inhibitors of the dapF in the lysine pathway of bacterial cell wall synthesis.